STUDY ON THE SOCIO-ECONOMIC BENEFIT OF LIMESTONE QUARRIES IN KABUPATEN REMBANG, CENTRAL JAVA PROVINCE - Sugiharto (NIM 221 04 037), Heru
Abstract : This study is aimed to determine the socio economic benefit of limestone quarries in Kabupaten Rembang, case study on PT. SAF as the biggest quarry operator in its mining lease (SIPD) area of 84.5 Ha. NSG analysis is used to calculate the economic rent, excess payment as well as externalities which consist of linkages on forward-backward, technological, payment to local government as well as final employees demand. In the period of 2000 to 2005 the economic rent was zero, the total excess payment was Rp. 3.51 billion (average Rp. 564.62 million/year). The linkages on backward was Rp. 10.4 billion (average Rp. 1.73 billion/year), technological was Rp. 362.48 million (average Rp. 60.41 million/year), the payment to Kabupaten Rembang government was Rp. 4.86 billion (average Rp. 0.82 billion/year) and final employees demand was Rp. 10.91 billion (average Rp. 1.82 billion/year). The NSG to Kabupaten Rembang was Rp. 28.91 billion (average Rp. 4.82 billion/year), the average growth of NSG was 13.95%/year. The average use of local resources for company input was 73.02% for human resources and 50.18% for intermediary input. The linkages on backward will raise from Rp. 10.39 billion to Rp. 11.30 billion (8.70% grow) and the average of utilizing of local resources for intermediary input per year will raise from 50.18% to 67.35% (17,17% grow) if PT. SAF gives the opportunities to local sectors to supply fuel, lubricant and grease. The linkages on technological had low impact because the community and sectors condition in Kabupaten Rembang were traditional. The payment to Kabupaten Rembang government will raise from Rp. 4.07 billion to Rp. 5.08 billion (25% grow) if the limestone price for tax calculation is based on market price. In the period of 2000-2005 PT. SAF contributed 83% to the total production of limestone of Kabupaten Rembang with the average production of 423,206 ton/year while the average production of limestone in Kabupaten Rembang was 522,373 ton/year. In the period of 2000 to 2005 the contribution of mining sector in GRDP of Kabupaten Rembang was on the average of 2.56%/year or Rp. 31.86 billion to Rp. 45.32 billion. Meanwhile the total GRDP was Rp. 1.37 trillion to Rp. 1.62 trillion. However according to the shift share analysis it was disclosed that the mining sector had progressive growth with the value of shift (PBij) positive, that was 19.04%.